2011
DOI: 10.3109/09540261.2010.546777
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to participation in mental health research: Findings from the Genetics and Psychosis (GAP) Study

Abstract: The aim of this study was to investigate why people with a first episode of psychosis choose or decline to participate in mental health research, using a qualitative study design. Participants were recruited via referrals from the Genetics and Psychosis (GAP) study. A total of 26 individuals with a first-episode of psychosis (nine of whom declined participation in the GAP study and 17 who participated) were individually interviewed and asked about their attitudes towards mental health research participation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 18 publications
3
34
0
3
Order By: Relevance
“…Those reasons are in agreement with those found in the literature [16,17,34]. We did not ask the participants directly for their motivation to participate, but those who expressed it spontaneously often stressed “helping other people or helping myself” as an important factor to participate in the trial, which were in accordance with the findings from Chong et al [15] and Roberts et al [18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Those reasons are in agreement with those found in the literature [16,17,34]. We did not ask the participants directly for their motivation to participate, but those who expressed it spontaneously often stressed “helping other people or helping myself” as an important factor to participate in the trial, which were in accordance with the findings from Chong et al [15] and Roberts et al [18].…”
Section: Discussionsupporting
confidence: 90%
“…Challenges and barriers regarding participation in research have been connected with timing of approach, practical barriers, conceptualization of mental health problems, concerns of potential harm, and negative influence of other patients [16,17]. Regarding reasons for participating in research Chong et al [15] found two main reasons for volunteering; 1) the possibility that I might get well, 2) I’m helping other patients like myself, and a similar study Roberts et al [18] found three main reasons; 1) helping other people, 2) helping science, 3) gaining a sense of hope.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have considered patient attitude towards engaging in research reporting facilitators and barriers such as altruism, reassurance about confidentiality, access to study centre, ethnic minority status, stigma and distrust in mental healthcare services. [11][12][13] Despite these advances, it is unclear whether research participation among people with mental disorders contributes to better clinical outcomes (as seen in physical healthcare) or if staff are more likely to approach patients about research if they have a relatively good prognosis.…”
Section: Found That Patientsmentioning
confidence: 99%
“…Na literatura internacional, há um crescente reconhecimento da importância, do direito e do valor do envolvimento de usuários da saúde mental em pesquisa (ROSE, 2003;GRIFFITHS;JORM;CHRISTENSEN, 2004;HAPPELL;ROPER, 2007;HOPKINS, 2008;NING;WEAVELL;WOODHOUSE, 2010;WOODALL;HOWAR;MORGAN, 2011;HANCOCK et al, 2012). Embora seja reconhecida a importância da inclusão ativa dos mesmos em pesquisa, valorizando o conhecimento advindo da experiência vivida, ainda são raras as iniciativas que os incorporam na equipe de pesquisa, como pesquisadores e/ou colaboradores.…”
Section: Participação De Usuários Em Pesquisaunclassified